Development Of Bilayer Tio2 Photocatalyst Systems Immobilized On Stainless Steel Plate And Their Physical And Photocatalytic Characterization - Chong, Kian Wei (2017)
The main weakness of TiO2 is that it needs UV light with wavelengths below 380 nm, which are considered hazardous to human being and expensive in term of cost, to activate its photocatalytic property. Therefore, various techniques had been used to improve the photocatalytic activity of TiO2• One of the method was doping or combining various types of metal oxides, metal sulfides, noble metal or metal ion withTiO2. Recently, adsorbent also had been used to co-doped with TiO2. In this research,TiO2 layer was immobilized onto the surface of NiO and chitosan adsorbents layer,which were supported onto stainless steel plate.